Total Knee Arthroplasty in Spondyloepiphyseal Dysplasia with Irreducible Congenital Dislocation of the Patella: Case Report and Literature Review - Sponer P (Dove Medical Press, 2021)
Pavel Sponer, Martin Korbel, Tomas Kucera Department of Orthopedic Surgery, Charles University, Faculty of Medicine in Hradec Kralove, Hradec Kralove, Czech RepublicCorrespondence: Pavel SponerDepartment of Orthopedic Surgery, Charles University, Faculty of Medicine in Hradec Kralove, Hradec Kralove, 500 03, Czech RepublicTel +420 495 833 566Fax +420 495 832 007Email sponer.p@seznam.czBackground: Spondyloepiphyseal dysplasia is the clinical term applied to a group of rare genetic disorders with primary involvement of the vertebrae and epiphyses, predisposing the afflicted individuals toward the premature development of osteoarthritis. There are few reports concerning joint replacement therapy in these patients, particularly describing the role of total hip arthroplasty. In this report, we describe the anatomical and technical aspects of spondyloepiphyseal dysplasia that must be considered during surgical planning and performance of total knee arthroplasty.Case Presentation: A 49-year old woman with a history of spondyloepiphyseal dysplasia suffered from severe osteoarthritis of the knee and irreducible congenital dislocation of the patella. After careful preoperative evaluations and planning, the knee joint deformity was solved by knee joint replacement with realignment of the extensor mechanism using quadricepsplasty. After 2 years of surgery, the patient showed no pain and was able to walk with the help of elbow crutches. The Hospital for Special Surgery knee score increased from preoperative 51 points to 85 points during the final follow-up. The postoperative range of motion increased to final flexion of 0– 115°.Conclusion: The advances made so far in the medical care for patients with skeletal dysplasia have improved their overall survival during adulthood. The case report described herein demonstrates the numerous challenges and technical aspects of a successful total knee arthroplasty in cases of spondyloepiphyseal dysplasia, highlighting the need to consider skeletal and soft tissue abnormalities of skeletal dysplasia during the planning and performance of joint replacement surgery.Keywords: spondyloepiphyseal dysplasia, patella dislocation, total knee arthroplasty